Length‐weight relationship of coral reef‐associated fishes from Gulf of Mannar and Palk Bay, Southeast Coast of India. (29th August 2020) - Kannan, Karuppiah; Kodeeswaran, Paramasivam; Kumar, Rajendran; Krishnamoorthy, Madhuri; Dharmaraj, Divya; Ethiraj, Kannapiran
Abstract: Length‐weight relationship parameter was estimated for eight coral reef‐associated finfish species from the Gulf of Mannar and Palk Bay, Eastern Indian Ocean. Fish samples were collected from the landings of trawlers with a cod‐end mesh size of 25–35 mm, operated at a depth ranging from 50–70 m off Tuticorin, Rameswaram and Thondi coasts on monthly basis between June‐2018 and July‐2019. Fish specimens were sampled by measuring total length (TL) and total weight (TW) with precision to 0.1 cm and 0.1 g respectively. A new maximum total length was recorded for Canthigaster solandri, Centriscus scutatus and Halichoeres stigmaticus from this study.